Filling the gap on Italian records of an invasive species : first records of the Blue Crab, Callinectes sapidus Rathbun, 1896 (Decapoda: Brachyura: Portunidae), in Latium and Campania (Tyrrhenian Sea) - Tiralongo, Francesco (Array, 2021)
Callinectes sapidus is considered one of the worst invasive species in the Mediterranean Sea. After its first observation in 1948, the species has colonized several Mediterranean areas. In this work, we report the first records of the species in Latium and Campania (northern-central and central Tyrrhenian Sea respectively), filling a gap in its distribution along the Italian coasts. We also provide a review of Italian records.